Stem cells in the treatment of osteoporotic fractures – medical science fiction or a therapy method in the future? - Grywalska, Ewelina; Grafka, Agnieszka; Putowski, Lechosław; Łopucki, Maciej; Roliński, Jacek (Menopause Review/Przegląd Menopauzalny, 2011)
Osteoporosis is typically a disease of the elderly, and with population aging it has become one of the most frequent and relevant health problems in this age bracket, especially among women. The greatest loss of bone mass occurs in women during perimenopause and is associated with oestrogen deficiency. The age-related decrease in bone mass could also reflect decreased osteoblasts secondary to an age-related loss of osteoprogenitors. The risk of fractures increases as women pass through the menopause. Osteoporotic fractures are associated with a profound temporary, and sometimes permanent, impairment of function and quality of life. Despite the rapid evolution of implant technologies and bone grafting techniques, there is still a great demand for novel bone replacement strategies. Cell replacement therapies represent an alternative solution. The use of mature cells such as osteoblasts is associated with several disadvantages such as the limited availability, donor site morbidity, dedifferentiation, and restricted proliferation potential. Bone marrow or adipose tissue-derived mesenchymal stem cells, which are the developmental progenitors for osteoblasts and for several other cell types, have been discovered for bone regeneration purposes. This review presents the possible applications of mesenchymal stem cells in the treatment of osteoporotic fractures.